Management of Chronic Osteomylitis - Aboud, Hamza Niama (AL-Kindy College Medical Journal, 2012)
Background : Bone infections is one of the most challenging orthopaedic complications, with considerable morbidity. There is significant impact on the life of the patients; socially, financially, physically, and mentally and it could be a limb-threatening complication. Osteomyelitis is a bone infection usually caused by bacteria, including mycobacteria, but mainly Staphylococcus aureus which is the most commonly responsible bacteria . Aim of study: To evaluate our management policy of chronic osteomylitis (C.O.M). Methods : 32 patients presented with different types &forms of chronic osteomyelitis in many sites of long & flat bones such as tibia , femur, ,humerus ,iliac bones and knee joint , which are not response to previous management . patients age…. range from 17 to 45 years old. Our study period extended from 2003 to 2009 with about one year follow up. our management include radical local bone debridement with multiple bone drilling and multiple washing by many antiseptic agents plus post operative specific antibiotic regime include triple intravenous broad spectrum antibiotics for two weeks , followed by parentral another two antibiotic regime for minimum 1.5 month up to 3 months, Results : From 32 patients involved in our study , 30 patients were found presented with non specific chronic osteomylitis in different form as following : 15 patients presented with tibial (C.O.M) & discharging sinus associated with offensive odder , 7 patients (21.8 % ) presented with (C.O.M) of femur, 7 patients (21.8 % ) presented with (C.O.M) of humerus mainly after internal fixation device application ( plate & screw )and one case (3.1 % ) presented with discharging pus from knee join as chronic septic arthritis . only two patients ( 6.2 % )presented with specific type of (C.O.M) such as T.B osteomylitis